The Narrative of Hosea’s Marriage to Gomer in Midrash Tradition: An Alternative Interpretation for Relationship and Morality Issues In the Contemporary Era - Nainggolan, Jisman; Soeoth, Esther Debora (Sekolah Tinggi Teologi Transformasi Indonesia, 2025)
This article discusses the narrative of the marriage of the Prophet Hosea to Gomer in the Midrash tradition as an alternative interpretation that offers relevance to issues of relationships and morality in the modern era. Melalui pendekatan hermeneutik Midrash, kisah tersebut ditafsirkan secara alegoris sebagai gambaran hubungan antara Tuhan dan Israel, yang ditandai oleh ketidaksetiaan manusia, namun selalu disertai dengan cinta dan pengampunan ilahi. The research findings indicate that the Midrashic tradition not only conveys theological messages but also serves as an effective medium for moral education and social critique. These findings have theological implications for contemporary relational dynamics, particularly concerning the values of loyalty, forgiveness, relationship restoration, and morality rooted in spirituality. This article emphasizes the urgency of revitalizing the legacy of ancient Jewish interpretations as the foundation for humane relational ethics amidst the increasingly complex global moral landscape.